Island and Mountain Ecosystems as Testbeds for Biological Control in the Anthropocene - Wyckhuys, Kris A. G.; Sanchez Garcia, Francisco J.; Santos, Ana M. C.; Canal, Nelson A.; Furlong, Michael J.; Melo, Maria C.; GC, Yubak Dhoj; Pozsgai, Gabor (Frontiers in Ecology and Evolution, 2022)
For centuries, islands and mountains have incited the interest of naturalists, evolutionary biologists and ecologists. Islands have been the cradle for biogeography and speciation theories, while mountain ranges have informed how population adaptation to thermal floors shapes the distribution of species globally. Islands of varying size and mountains’ altitudinal ranges constitute unique ‘natural laboratories’ where one can investigate the effects of species loss or global warming on ecosystem service delivery. Although invertebrate pollination or seed dispersal processes are steadily being uncovered, biological control research is lagging. Yet, observations of a wider niche breadth among insect pollinators in small (i.e., species-poor) islands or at high (i.e., colder) altitudes likely also hold for biological control agents but wait to be examined. In this Perspective piece, we draw on published datasets to show that island size alone does not explain biological control outcomes. Instead, one needs to account for species’ functional traits, habitat heterogeneity, host community make-up and phenology, site history or even anthropogenic forces. Meanwhile, data from mountain ranges show how parasitism rates of Noctuid moths and Tephritid fruit flies exhibit species- and context-dependent shifts with altitude. Nevertheless, future empirical work in mountain settings could clarify the thermal niche space of individual natural enemy taxa and overall thermal resilience in biological control. We further discuss how global databases can be screened, while ecological theories can be tested, and simulation models defined based upon observational or manipulative assays in either system.